Responsible management and taoism. Volume 2, - Zu, Liangrong (Emerald Publishing Limited, 2023)
This second volume builds upon the core themes explored in volume one, which focused on 'Managing Responsibly for Sustainable Business Development in the VUCA World'. This volume explores the transformative power of management education. It delves into the crucial shift from knowledge-inquiry to wisdom-inquiry, advocating for a holistic and insightful approach in management education that transcends traditional boundaries. This volume further examines how the integration of corporate social responsibility (CSR) and sustainability in management education is essential for nurturing future leaders who are equipped to address the pressing challenges of our time. An integral part of responsible management education is its contribution to the achievement of the Sustainable Development Goals (SDGs). This volume discusses the profound impact that responsible management education can have on advancing the SDGs, highlighting the interconnectedness between education, responsible business practices, and sustainable development. It also explores the vision for a sustainable and inclusive world through the implementation of 'Our Common Agenda', a ground-breaking initiative spearheaded by the United Nations, which emphasizes the importance of a new social contract. When embracing the profound wisdom of Taoism and integrating responsible management education into the fabric of our educational systems, we can pave the way for a sustainable, inclusive, and prosperous world for all. This volume is part of a two-volume series, together providing a comprehensive exploration of responsible management, Taoism, and their transformative potential in overcoming challenges in the VUCA era.